Developing Nature and Culture-Based Tourism in Kedung Murung Village: Community Empowerment Approaches - Anindyasari, Dinar; Indana, Khoiru; Safitri, Apdila; Najih, Riyan Riyadlun; Aprylasari, Dede (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
Kedang Murung Village has strategic potential to develop nature and culture-based tourism, with Tanjung Sarai Lake as the main attraction. The uniqueness of nature, local wisdom, and rich traditions are essential to forming an authentic tourist destination identity. Active community involvement supported by high social solidarity shows the community's readiness to support sustainable tourism initiatives. As a result, there is a real contribution to increasing community income and local economic growth. However, tourism development faces several obstacles, such as limited supporting infrastructure, minimal budget, and low managerial capacity of the community in managing tourism businesses. This study recommends strengthening synergy between the village government, the private sector, and local communities through a collaborative approach to planning and implementing tourism programs. Information technology, especially digital media, is essential to increase promotion effectiveness and market reach. In addition, training and mentoring for the community in managing small and medium enterprises (MSMEs) need to be intensified to increase entrepreneurial capacity and strengthen the competitiveness of the village as a tourist destination. These efforts are expected to enhance the local economy and support environmental conservation and sustainable cultural preservation.